Tecnologías de la información y la comunicación (TIC’s) y nociones lógico - matemáticas en niños de preparatoria de la Unidad Educativa Lauro Damerval Ayora de la ciudad de Loja, período 2022 - 2023 - Córdova Sánchez, Paola Alexandra (2023)
The use of TIC's in education is important in all areas of human life, they provide a comprehensive pedagogical learning and can contribute to society in different ways, generating more learning in less time and especially for the processes of innovation in education; Therefore, this work aims to determine whether the use of TIC's improves the logical-mathematical notions in high school children of the Lauro Damerval Ayora Educational Unit of the city of Loja, for this work a quasi-experimental design was applied, with a mixed approach and descriptive scope; the methods used were inductive, deductive, analytical and synthetic that facilitated the choice of information for the construction of all the research work. Among the techniques and instruments for this work were observation and the EVAMAT-0 battery by Jesús García Vidal, which evaluates geometry, quantity and counting, and problem solving. As a sample, 19 children were selected; achieving to diagnose in the pretest 100% of children with difficulties in logical-mathematical notions and after having carried out activities with the use of TIC's directed to children, new results are demonstrated in the post-test, finding 77.1% in the medium mathematical competence and 22.8% of children in the high mathematical competence, confirming in this way that the use of ICT's improves notably this problem and increases the learning process in the area of logical-mathematical notions. Keywords: educational tools, logical-mathematical notions, information technologies, TIC’s.